2012
DOI: 10.5402/2012/469019
|View full text |Cite
|
Sign up to set email alerts
|

pH and Antimicrobial Activity of Portland Cement Associated with Different Radiopacifying Agents

Abstract: Objective. The aim of this study was to evaluate the antimicrobial activity and pH changes induced by Portland cement (PC) alone and in association with radiopacifiers. Methods. The materials tested were pure PC, PC + bismuth oxide, PC + zirconium oxide, PC + calcium tungstate, and zinc oxide and eugenol cement (ZOE). Antimicrobial activity was evaluated by agar diffusion test using the following strains: Micrococcus luteus, Streptococcus mutans, Enterococcus faecalis, Pseudomonas aeruginosa, and Candida albic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
30
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 29 publications
4
30
0
1
Order By: Relevance
“…It has been reported that several microorganisms are very sensitive to alkaline media, among them, C. albicans. 41 We suggest that this is the basis for the fungicidal character of Bi 2 O 3 nanoclusters. Additionally, we cannot discard antifungal activity mechanisms involving free radicals, due to the presence of CO 2 in the culture media 42 and the inherent α-Bi 2 O 3 NPs photocatalytic properties.…”
Section: Discussionmentioning
confidence: 85%
“…It has been reported that several microorganisms are very sensitive to alkaline media, among them, C. albicans. 41 We suggest that this is the basis for the fungicidal character of Bi 2 O 3 nanoclusters. Additionally, we cannot discard antifungal activity mechanisms involving free radicals, due to the presence of CO 2 in the culture media 42 and the inherent α-Bi 2 O 3 NPs photocatalytic properties.…”
Section: Discussionmentioning
confidence: 85%
“…The antimicrobial activity evaluation showed similar results for all the microorganisms evaluated. The addition of substances to MTA aiming to improve its antimicrobial effect has been studied [27][28][29] . Odabas et al 29) demonstrated that silver addition to MTA improves its antimicrobial property.…”
Section: Discussionmentioning
confidence: 99%
“…Saatchi 27) et al observed that the inclusion of potassium iodide does not alter the antimicrobial effect of MTA. GuerreiroTanomaru et al 28) showed that Portland cement-based materials with the addition of different radiopacifiers (bismuth oxide, calcium tungstate, and zirconium oxide) presented antimicrobial activity and pH similar to pure PC. The alkaline pH of MTA may be important for the calcium carbonate formation, which could contribute to the sealing ability of MTA 30) .…”
Section: Discussionmentioning
confidence: 99%
“…The solubility of the components of Portland cementbased endodontic restoratives impacts upon their sealing capacity, mechanical stability, antimicrobial properties, biocompatibility and bioactivity [18][19][20][21] . For example, soluble calcium and silicate species are acknowledged to stimulate bone tissue regeneration 18,19) .…”
Section: Discussionmentioning
confidence: 99%